Kiss the girls [videorecording (DVD)] - Freeman, Morgan; Judd, Ashley; Elwes, Cary, 1962-; Fleder, Gary; Patterson, James, 1947- (Widescreen DVD collection., 1998)
Washington DC detective Dr. Alex Cross (Morgan Freeman) travels to North Carolina to investigate the apparent kidnapping of his niece (Gina Ravera). Aided by escaped kidnapee Kate McTiernan (Ashley Judd), Cross hunts down the kidnapper, who operates under the pseudonym "Cassanova."